Pengaruh Kepemimpinan, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Pada PT. Antilope Madju Puri Indah) - Friska Simanjuntak; Achmad Tarmizi; Didin Hikmah Perkasa (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Performance is a work achievement or the result of a person's work based on the quantity and quality achieved in carrying out its functions in accordance with the responsibilities received. The main objective of this study is to determine the effect of leadership, work discipline and work environment on employee performance (study at PT. Antilope Madju Puri Indah). The research design uses causal quantitative methods, namely knowing the influence of the variables studied. The objects in this study are employees of PT. Antilope Madju Puri Indah as many as 100 respondents. The data collection tool uses a questionnaire that has been tested for validity and reliability which is distributed via the Google form. Data analysis was carried out using Smart-PLS (Partial Least Square) through testing the outer model, inner model and hypothesis testing. The results showed that the Leadership Variable had an effect on Employee Performance, Work Discipline Variable had no effect on Employee Performance and Work Environment Variable had had an effect on Employee Performance at PT. Antilope Madju Puri Indah.